The impact of exogenous l-arginine on cardiohaemodynamics and heart rhythm variability in patients with coronary heart disease after community-acquired pneumonia - Mykhailovska, Natalia; Kulynych, Tamila (ScienceRise: Medical Science, 2017)
Aim of the work: to study the influence of exogenous L-arginine on structural-functional indices of heart, intensity degree of myocardium coronary changes and heart rhythm variability in patients with coronary heart disease after community-acquired pneumonia. Methods of research: the open prospective study included 60 patients with CHD, exertional angina, 2-3 f.c., who underwent community-acquired pneumonia of 3 clinical group (men – 34, women – 26, age median 72,50 (66,00; 75,00) years old). All patients underwent clinical examination, included clinical-laboratory methods of examination, two-dimensional echocardioscopy and impulse-wave dopplerography, daily monitoring of ECG by Holter at admission to hospital and in 3 months. After singing the informed consent, the patients were randomized in 2 groups. Main group included 30 persons, who received L-arginine in addition to basic CHD therapy, 30 patients of control group received only basic therapy. Results of research: patients of main group at secondary examination in three month demonstrated a tendency to decrease of final-diastolic volume of LV, reliable increase of fraction of left ventricle emission by 4,44% (р<0,05), and decrease of mean pressure in pulmonary artery was more significant (8,33% vs 2,94%; р<0,05). The inclusion of L-arginine in the scheme of CHD treatment favored the reliable (р<0,05) decrease of tachycardia duration by 49,77%, number of ventricular extrasystoles by 63,2%, duration of ST segment depression by 56,52%, increase of general heart rhythm variability (rMSSD – by 70,00%, ТР – by 97,42%) and decrease of LF/HF index by 11,67% at the expanse of activity of parasympathetic component comparing with patients, who received only basic therapy. Conclusions: the addition of L-arginin to the basic therapy in patients with IHD has the positive influence of cardiohemodinamics, favors the decrease of intensity degree of coronary changes and normalization of sympatho-parasympathetic balance of vegetative nervous system